Karakterisasi Sifat Fisikokimia Tepung Kacang Hitam dan Aplikasinya pada Brownies Panggang - Eko Hari Purnomo; Achmad Nasir Ginanjar; Feri Kusnandar; Cynthia Andriani (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Average protein intake of Indonesian is relatively low. Black bean (Phaeseolus vulgaris) is one of the Indonesia local pulses containing high content of protein (16.6% wet basis). Black bean our has a potential as a substitute for wheat our in bakery products such as brownies. The objective of this research was to determine suitable milling procedure of black bean and to evaluate black bean our substitution on physical, chemical, and sensory effects of of brownies. Two different milling methods (dry and wet milling) were studied to produce black bean our after different soaking times (6, 12, and 18 hours). Dry milling method was optimum after 12 hours of soaking. Black bean our contained 23.9% of protein, 62.61% of carbohydrate. The yield of milling process was 49.39% and the our whiteness was 57.74. Substitution 25% of black bean our in brownies making did not decrease brownies characteristics. The brownies had 7.8% of protein content, 513.13 gram force of hardness, 0.71 of elasticity, 0.36 of cohesiveness, with acceptable sensory qualities.